Effects of sintering temperatures on microstructure and wear resistance of iron-silica composite - Amir, A. (American Institute of Physics Inc., 2015)
Ceramic particle reinforced into metal base matrix composite has been reported to produce higher strength and wear resistance than its alloys because the ceramic phases can strongly resist abrasion. In this study the iron matrix was reinforced with two compositions of 20 and 25 wt. fine silica particles. The compacts were produced by using powder metallurgy fabrication technique and sintered at three sintering temperatures: 1000, 1100 and 1200°C. Effects of various sintering temperatures on microstructures and the composite's wear resistance were evaluated via optical and SEM microscopy. Both compositions were also subjected to ball-on-disk wear test. The results showed the reinforcement weight fraction of 20 wt. of silica and sintering temperature at 1100°C exhibited better result, in all aspects. It possessed higher mechanical properties, it's microstructure revealed most intact reinforcing region and it displayed higher wear resistance during wear test. © 2015 AIP Publishing LLC.